Effect of anticancer activity of aripiprazole main metabolite OPC-14857 on malignant glioblastoma - Shuhei Nakao; Yuki Uemichi; Shuji Nagano; Miyuki Mabuchi; Shiho Ohmori; Daichi Enomoto; Takehiko Ueyama; Tadashi Shimizu (PLoS ONE, 2026)
Glioblastoma is an incurable and highly malignant brain tumor that poses challenges in surgical and chemotherapeutic treatments. Aripiprazole (ARP), an antipsychotic drug, exerts cytotoxic effects against various cancers. In the present study, we compared the inhibitory effect of ARP on cell proliferation with that of its main metabolite, OPC-14857 (OPC), using glioblastoma cell lines (U251, T98G, and U87 cells) to explore their potential for repurposing against brain tumors. Both demonstrated more potent anticancer activity than temozolomide, the current standard clinical therapy for malignant glioblastoma. Additionally, we assessed their effects on the cell cycle, cytoskeleton, cell migration, and protein expression. The anti-proliferative and anti-migratory activities of OPC were similar to those of ARP. Moreover, there were no differences in the effects of cell death inhibitors on the anticancer activities of ARP and OPC. However, the two compounds exhibited distinct activity profiles. Exposure to OPC was suggested to induce G2/M phase cell cycle arrest and to suppress cell proliferation and migration, potentially by affecting actin and altering its subcellular localization. ARP and OPC enhanced doxorubicin (DOX) efficacy, likely via P-glycoprotein inhibition; known for ARP, suggested for structurally similar OPC. Treatment with ARP or OPC reduced the expression of survivin, an anti-apoptotic protein, suggesting an increase in apoptotic susceptibility. Although our observations were limited to in vitro studies, our findings suggest that OPC may have sustained anticancer effects even when ARP is metabolized in humans. Therefore, if ARP can be used for drug repurposing in glioblastoma, the long-term effects of OPC could be anticipated.